Correlating Parameters With Hydrogen Purity And Recovery By Psa In Hydrogen Purification From Syngas - Zakaria, Nurul Asyiqin (Universiti Sains Malaysia, 2022)
The pressure swing adsorption model (PSA) on ASPEN Adsorption platform using Cu-BTC as the adsorbent was used to simulate the hydrogen purification performances (purity and recovery) from binary syngas feed (containing 80% H2 and 20% CO2). Results showed the simulated breakthrough curves from the Aspen simulation fit well with the experiment data from the literature. The results also showed that increasing adsorption pressure and prolonging adsorption time would lead to decrease of both hydrogen purity and recovery. Meanwhile, increasing hydrogen feed concentration, increased the hydrogen purity but reduced its recovery. The optimization was also carried out to find the maximum product purity and recovery. The optimized purity and recovery were recorded at 90.12% and 93.22% respectively when the adsorption pressure of 2 bar, adsorption time of 150s and hydrogen feed concentration of 75% were used. Through a maximisation section, this model was confirmed could meet the standard hydrogen purity for fuel cells by setting the adsorption pressure, adsorption time and hydrogen feed concentration to 2 bar, 102.48s and 80% respectively.